Rural Older Adults' Perspectives of Activities to Support Cognitive Health. Issue 3 (2nd July 2020) - Bacsu, Juanita-Dawne; Viger, Marc; Johnson, Shanthi; Novik, Nuelle; Jeffery, Bonnie
ABSTRACT: Existing cognitive health literature focuses predominately on understanding the pathology and clinical treatment of older adults with dementia rather than cognitive health promotion and preventative activities. In addition, most of the work in the area remains urban-centric with little focus on cognitive health in rural communities. This study examined rural seniors' perspectives of activities that they identified as supporting their cognitive health. Using community-based research and an ethnographic methodology, participant observation and semi-structured interviews were conducted with 42 older adults in rural Saskatchewan, Canada. Participants discussed a variety of activities that they viewed as supporting their cognitive health. In particular, cognitive health promotion was identified as being strongly linked to keeping one's brain active, thinking positively, mingling with others, and managing daily affairs. This study's findings suggest that there is a need to move beyond focusing solely on clinical interventions to including older adults' perspectives of preventative activities and cognitive health promotion.